2004
DOI: 10.1046/j.1471-4159.2004.02347.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of microglial activation by α7 nicotinic receptors

Abstract: Almost all degenerative diseases of the CNS are associated with chronic inflammation. A central step in this process is the activation of brain mononuclear phagocyte cells, called microglia. While it is recognized that healthy neurons and astrocytes regulate the magnitude of microglia-mediated innate immune responses and limit excessive CNS inflammation, the endogenous signals governing this process are not fully understood. In the peripheral nervous system, recent studies suggest that an endogenous 'cholinerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
440
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(473 citation statements)
references
References 34 publications
25
440
4
4
Order By: Relevance
“…This anti-inflammatory potential of acetylcholine and nicotine is based on the inhibition of the NF-κB pathway through a specific nicotinic anti-inflammatory pathway' dependent on the alpha7nAChR (Wang et al, 2004). The inhibition of TNF production in LPS-stimulated microglial cultures is also associated with a reduction in the activation of ERK and p38MAPK (Shytle et al, 2004;Suzuki et al, 2006) (Fig. 2).…”
Section: Inflammation In Neurodegenerative Disordersmentioning
confidence: 96%
See 3 more Smart Citations
“…This anti-inflammatory potential of acetylcholine and nicotine is based on the inhibition of the NF-κB pathway through a specific nicotinic anti-inflammatory pathway' dependent on the alpha7nAChR (Wang et al, 2004). The inhibition of TNF production in LPS-stimulated microglial cultures is also associated with a reduction in the activation of ERK and p38MAPK (Shytle et al, 2004;Suzuki et al, 2006) (Fig. 2).…”
Section: Inflammation In Neurodegenerative Disordersmentioning
confidence: 96%
“…Nicotine induces anti-inflammatory mechanisms that diminish local inflammatory responses (Hellstrom-Lindahl et al, 2004a;Streit, 2002;Wang et al, 2000a, b). Among other, nicotine abrogates the production of TNF in culture of microglia through a mechanism dependent on ERK and p38 MAPK (Shytle et al, 2004;Suzuki et al, 2006). Experimental models of AD indicate that alpha7nAChR is the central core of the nicotine-mediated neuroprotection.…”
Section: Epidemiological Implications Of Nicotine In Neurodegenerativmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, others have reported that administration of acetylcholine inhibits LPSinduced TNF-α release by a reduction in phosphorylation of MAPKs. This inhibitory effect of acetylcholine is blocked by α-bungarotoxin, a specific antagonist of alpha 7 nAChR [17] . Our present study indicates that α-bungarotoxin blocks the effect of carbachol on ERK1/2 and JNK activation and the expression of VE-cadherin and ICAM-1 in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%